2011
DOI: 10.1088/0031-9155/56/22/020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of internal dosimetry factors for three classes of adult computational phantoms with emphasis on I-131 in the thyroid

Abstract: S values for 11 major target organs for I-131 in the thyroid were compared for three classes of adult computational human phantoms: stylized, voxel and hybrid phantoms. In addition, we compared Specific Absorbed Fractions (SAFs) with the thyroid as a source region over a broader photon energy range than the x- and gamma-rays of I-131. S and SAF values were calculated for the International Commission on Radiological Protection (ICRP) reference voxel phantoms and the University of Florida (UF) hybrid phantoms by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…Figure 1 indicates that the S values calculated in this study (using F6 and *F8 tally) were in good agreement with those from Lamart et al [6]. The results for each radiopharmaceutical come in the following sections.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Figure 1 indicates that the S values calculated in this study (using F6 and *F8 tally) were in good agreement with those from Lamart et al [6]. The results for each radiopharmaceutical come in the following sections.…”
Section: Resultssupporting
confidence: 87%
“…The S value in turn, is defined as the mean absorbed dose to the target organ ( r T ) per unit of nuclear transition of the relevant radionuclide in the source region considered [5, 6]: \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$$D\left( {r_T } \right){\rm \; }=\mathop \sum \limits_{r_S } S\left( {r_T \leftarrow r_S } \right)\tilde A\left( {r_S } \right) $$\end{document} …”
Section: Methodsmentioning
confidence: 99%
“…The thyroid is the major contributor to the lung dose; hence the shorter distances between the thyroid and lungs for voxel phantoms would result in a greater lung dose. Lamart et al (2011) reported the CLDs between the lungs and thyroid in female phantoms which have different mean distances; (14.5 and 20.4 cm) for the ICRP voxel and ORNL phantom, respectively. This shift demonstrates the approximately fourfold greater lung dose for the voxel phantoms.…”
Section: Discussionmentioning
confidence: 99%
“…1): Sfalse(rTrSfalse)=1.602×10-101Mfalse(rTfalse)[Eγ(γT)Yγ+Eβ(rT)Yβ] where 1.602 × 10 −10 is the number of joules per MeV. We previously reported the details of the calculation method (Lamart et al 2011). …”
Section: Methodsmentioning
confidence: 99%